The Impact of Academic Advising Activities on International Students’ Sense of Belonging - Yuan, Xiao; Yang, Yang; McGill, Craig (Journal of International Students, 2023)
Research on international students suggests they have a low sense of belonging at the U.S. institutions they attend. This study examined whether academic advisor’s cultural empathy, advisor-advisee rapport, and international students’ advising satisfaction influenced international students’ perspectives of belonging to the institution. We further examined whether cultural empathy and advisor-advisee rapport mediated the effect of advising satisfaction on international students’ sense of belonging. The cross-sectional quantitative study used a convenience sample of 209 international students enrolled in two institutions in the United States. Results indicated that cultural empathy and student advising satisfaction had a statistically significant influence on the sense of belonging, not advisor-advisee rapport, and cultural empathy mediated the effect of advising satisfaction on sense of belonging. We offered recommendations for institutions and academic advisors when working with international students.